Evaluation of Long Term Performance for Initial Public Offerings (IPO) in Malaysia: A Fama-French Method - Abu Bakar, Nashirah; Rosbi, Sofian (International Journal of Scientific Research and Management (IJSRM), 2019)
The objective of this study is to evaluate performance of initial public offerings for 16 sharia compliant companies listed on the Malaysia Stock Exchange. Data of stock price are collected from Thomson Reuters Datastream for 36 months starting from January 2016 until December 2018. The method implemented is using Fama-French approach that evaluates expected return with three factors namely Market Risk Premium (MRP), Small Minus Big (SMB) and High Minus Low (HML). Result shows the abnormal return for 36 months is -3.399 which indicates negative value. The negative value of y-intercept gives interpretation that market (FTSE Bursa Malaysia KLCI) performed better than portfolio. The findings of this study will help investors to understand the financial dynamic behavior in Malaysia Stock Exchange. In addition, it will help investors to select appropriate financial assets for investment portfolio in gaining better return.